Perhitungan PDRB Hijau Sektor Kehutanan Dari Depresiasi Hutan Di Kabupaten Tanah Bumbu - Mega Rumita; M. Anshar Nur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to know : (1) to identify the value of depletion, degradation, andforest depreciation in Tanah Bumbu District. (2) can see the value of forestry sector GreenGDRP in Tanah Bumbu District.According to the explanation in the form of descriptive research, this type of research usessurvey methods and type of data in the form of quantitative data, which includes somecalculations using the concept of Green GDRP. The data used is secondary data.The results showed that the value of the Green GDRP is smaller than Conventional GDRP.The results of the 2016 forestry sector Green GDRP calculation amounted to Rp. 99.327,82Million, in 2017 amounting to Rp. 93.046,67 Million, and in 2018 amounting Rp. 97.211,59Million.